(untitled) (Western European Journal of Medicine and Medical Science, 2025)
Hypothyroidism is an endocrinological disease that manifests itself as insufficient production of thyroid hormones. There are three degrees of the disease: primary, secondary and tertiary hypothyroidism in women and men. Hypothyroidism is one of the most common diseases of the endocrine system. Despite the well-studied etiology, pathogenesis and simple diagnosis, in some cases the disease remains unrecognized for a long time, which is due to the slow increase in thyroid deficiency and, accordingly, the severity of the clinical picture. The biological action of thyroid hormones is very diverse: by activating the transcription of numerous genes, they participate in the regulation of basic physiological processes in the body, therefore their deficiency can manifest itself in a wide variety of clinical manifestations and symptoms and imitate diseases of almost all body systems